ON THE SUSTAINABILITY OF CURRENT ACCOUNT DEFICITS IN CAMEROON - Edouard T. Djeutem; Pierre E. Nguimkeu (International Journal of Economics and Financial Issues, 2013)
Two approaches are used to analyze the sustainability of the current account deficits of Cameroon in order to find out whether current economic policies are sound enough to guarantee the country’ s financial solvency. The first uses a structural procedure to compare current account deficits relative to an optimal benchmark using the Campbell-Shiller’s methodology. The second uses a reduced form approach to test for intertemporal budget constraint through cointegration tests between imports and exports plus net transfer payments on foreign obligations. Our results suggest that the current account imbalances for Cameroon based on data from the period 1970-2002 are “excessive” and the deficits are currently unsustainable.